Determination Of Total Flavonoid Content In Bangle Plant (Zingiber Montanum)Extraction Results - Sri Hastuti Virgianti Pulukadang; Sitti Rahmawati; Tri Santoso; Siti Fatimah; Sitti Aminah; Purnama Ningsih; Magfirah (Postgraduate, University of Mataram, 2024)
The bangle plant (Zingiber montanum) is a plant that has been used traditionally as a medicinal ingredient, both for prevention and treatment by the community. Parts of the bangle plant contain active compounds that act as antioxidants, one of which is flavonoids. This research aims to determine the total flavonoid content in bangle plants from the extraction results measured using a UV-Vis spectrophotometer. The method for separating flavonoid levels used is maceration. The research results showed that positive test results were obtained for flavonoid compounds in bangle rhizomes as evidenced by qualitative test results which produced a red color in the sample extract and the average total flavonoid content in bangle rhizomes from the extraction results measured using a UV-Vis spectrophotometer was 23. 1mg/100g.